2013
DOI: 10.1590/s1983-40632013000100010
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicação in vitro de plantas juvenis de mamoeiro

Abstract: O método de propagação seminífera do mamoeiro (Carica papaya L.) apresenta uma mistura de genótipos com influência marcante nos custos de produção, qualidade e rendimento dos frutos, prevalecendo devido à inexistência de protocolos eficientes de propagação vegetativa. Neste contexto, a cultura de tecidos surge como uma alternativa promissora, pois poderá fornecer aos produtores mudas com sexo definido, alto padrão de qualidade e em quantidade suficiente para atender à demanda comercial, em qualquer época do an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
2
0
2
Order By: Relevance
“…Micropropagated woody species generally have a low multiplication rate as observed in Libidibia ferrea, which the highest rate (27.75) was obtained when the explants were grown in the presence of 3.96 µM of BAP (Silva, 2019). Although BAP is one of the most widely used phytoregulators to increase the in vitro multiplication rate, this cytokinin does not always have a positive effect for all species (Vidal et al, 2013), a statement that corroborates with the data obtained in the present study with E. involucrata. This result confirms therefore the importance of adjusting the propagation protocols in order to increase the mass production of plants (Silva, 2019).…”
Section: Resultssupporting
confidence: 92%
“…Micropropagated woody species generally have a low multiplication rate as observed in Libidibia ferrea, which the highest rate (27.75) was obtained when the explants were grown in the presence of 3.96 µM of BAP (Silva, 2019). Although BAP is one of the most widely used phytoregulators to increase the in vitro multiplication rate, this cytokinin does not always have a positive effect for all species (Vidal et al, 2013), a statement that corroborates with the data obtained in the present study with E. involucrata. This result confirms therefore the importance of adjusting the propagation protocols in order to increase the mass production of plants (Silva, 2019).…”
Section: Resultssupporting
confidence: 92%
“…The addition of plant growth regulators in the culture media compensate for any possible deficiencies of the hormonal endogenous levels in the explants (VIDAL et al, 2013). Among the plant growth regulators, gibberellins show physiological activities in the induction of seeds germination and in breaking dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…(Moura, Titon, Miranda, Moreira, & Oliveira, 2012) and Hancornia speciosa Gomes (Oliveira, Freire, & Aloufa, 2016), whose explants were more responsive in MS culture medium devoid of BAP and NAA. Vidal, Diniz and Silva (2013) found that BAP, despite being widely used in the in vitro multiplication phase, may not exert a satisfactory effect, depending on the species studied. Mallón, Rodríguez-Oubina and González (2011) attributed this behavior to the concentrations of endogenous auxins and cytokinins being sufficient to induce plant development in vitro.…”
Section: Resultsmentioning
confidence: 98%